Contribution of self-efficacy and optimism to work-family enrichment of working wives in Surabaya City - Burhan, Daniel; Wardani, Ria; Kuntari, C.M. Indah Soca R. (Insight: Jurnal Ilmiah Psikologi, 2024)
Generally, the workforce is dominated by men, but data from the Statistics Indonesia highlight a different trend in Surabaya City as the number of working women is increasing. These working women also include married women who have responsibilities both at work and in their families. The relationship between these two responsibilities is often negatively viewed. The work-family enrichment theory explains that there are positive contributions that can be made between these two roles. The theory suggests that psychological factors contribute to the formation of work-family enrichment. Providing an overview of the contributions of optimism and self-efficacy to work-family enrichment is the aim of this study. It involved 120 working women in Surabaya City. Its research subjects were married women, aged between 20 and 39 years, had been working for at least 1 year, and worked full-time for a standard workday of 8 hours or 40 hours per week. The samplings of this study were obtained by convenience sampling. It utilized the Work-family Enrichment Scale (36 items, α=0.97), the Optimism Scale (10 items, α=0.63), and the Self-efficacy Scale (8 items, α=0.86). A multiple linear regression was implemented to test the hypotheses of this study. It reveals a positive relationship between optimism & self-efficacy and work-family enrichment. Self-efficacy and optimism together accounted for 63.1% of their contribution. It suggests the importance for the working wives to develop their optimism and self-efficacy to increase work-family enrichment and achieve a satisfactory balance between work and family. Keyword: Optimism; self-efficacy; work-family enrichment.